(untitled) (Al-Farooq Journal of Sciences, 2026)
This study was conducted in selected departments of Tripoli Medical Center to assess the microbiological quality of hospital indoor air and to investigate bacterial and fungal contamination as potential sources of hospital-acquired environmental infections. Air samples were collected from five major hospital departments: the Emergency and Reception Department, the Intensive Care Unit (ICU), the Obstetrics and Gynecology Department, the Surgical Intensive Care Unit, and the Neonatal Intensive Care Unit (NICU). A total of 18 microbial isolates were recovered and identified. The microbiological analysis revealed that Staphylococcus epidermidis was the predominant bacterial species, with a prevalence rate of 88.9%, followed by Staphylococcus aureus (61.6%). Micrococcus spp. accounted for 27.8% of the isolates, while Pseudomonas aeruginosa represented 22.2%. Escherichia coli was detected in 16.7% of the samples, and Pseudomonas spp. was identified in 9.38%. The remaining bacterial species were detected at relatively low frequencies, ranging from 0% to 11%. Among the fungal isolates, Candida spp. was the most prevalent species, accounting for 22.2% of the total fungal isolates, whereas the other fungal species were detected at comparatively lower frequencies. The findings of this study indicate the presence of potentially pathogenic microorganisms in the indoor air of hospital departments, highlighting the importance of continuous air quality monitoring and the implementation of effective infection control measures to reduce the risk of airborne transmission and hospital-acquired infections.